PERAN GURU DALAM PEMBELAJARAN MENULIS PUISI MELALUI KEGIATAN LITERASI DI MI AL QUR’AN JABALKAT - Nafsi, Filzatun; Retno Intan Kuswari (JIPSKi: Jurnal Ilmu Pendidikan dan Studi Keislaman, 2024)
Literacy activities is a way for students to recognize, understand and apply the knowledge they have acquired during the learning process. Literacy activities can develop vocabulary and knowledge in various things. Teachers are not only educators, but also mediators, learning resources, facilitators, models and role models. Researchers maximize this literacy activity through poetry writing activities in Indonesian language classes. The researcher aims to determine the role of teachers in learning to write poetry through literacy activities at the elementary school. This research uses a qualitative descriptive approach. Literacy activities in learning to write poetry can increase students' self-confidence. Students will produce their own written works. Teachers provide encouragement or motivation so that they not only read but also write in literacy activities. The teacher will also be a facilitator for them so that their works are interesting and can be read by many people. This is evidenced by the existence of a poetry anthology entitled Persembahan Untuk Para Pejuang Negri and Karya Untuk Negriku.